Law Construction in Modern Society - Arief, Sofyan (The Indonesian Journal of International Clinical Legal Education, 2019)
Law as a social construction instrument should be able to improvesocial system and face the challenge of this changing era. However,what happens in our society nowadays shows that people tend to haveless trust to law. It is proven by opponents of inadequate quality of lawas the agent of social construction and the substantive justice.Additionally, the anxiety of legitimating crisis occurs. Law as a media ofsocial construction, which is aiming at creating fair and prosperoussociety, seems problematic to be accepted. In this case, realizing thecause of people’s problems in interpreting and accepting the purposeof law as a social construction instrument becomes the importantmatters. The level of people’s education leads to the low law awareness.The education systems, the pattern of regulations socialization, thelimitation of public information access may lead to low recognitiontoward law. Regarding the problems abovementioned, educationbecomes one of alternative solution. It is expected that the higherpeople’s law awareness, the lower people’s opportunity to break thelaw. Thus, public education may promote the implementation ofconstruction of modern society.